Wireless energy harvesting: Empirical results and practical considerations for Internet of Things. (1st November 2018) - Sanislav, Teodora; Zeadally, Sherali; Mois, George Dan; Folea, Silviu Corneliu
Abstract: The continuous growth of the Internet of Things (IoT) has led to the development of different types of wireless sensors that are used for monitoring and actuation, communicating with each other and with various infrastructures through the Internet. The long-term and self-sustainable operation of these wireless sensors is a key factor when designing networks using them. To prolong the lifetime of these sensors, various approaches that are capable of harvesting the required energy from various sources have been proposed over the last few years. Wireless Energy Harvesting (WEH) technology is one of them which shows promise in terms of availability, ease of implementation, and cost. We investigate the current status of WEH technology for IoT-enabled sensors. In particular, we evaluate the energy characteristics and operation of two types of environmental wireless sensors (one based on Bluetooth Low Energy (BLE) communication and the other on the UDP protocol) that are powered by a wireless energy harvesting element and operate in the IoT environment. Our literature review on WEH for IoT revealed that despite significant advances that have been made in the design and development of wireless power harvesting elements, achieving self-sustainable wireless sensors for IoT remains a significant challenge. Finally, we also highlight some research challenges of WEH for IoT that need to be addressed in the future.